Exigência e biodisponibilidade de manganês para frangos de corte - Mariana Masseo Saldanha (2019)
The objective of this study was to evaluate the manganese (Mn) requirement for broilers in the periods of one to 20 and 20 to 40 days of age and the relative bioavailability (RB) of Mn supplemented as sulphate Mn (MnSO4) and Mn proteinate (MnProt). Two experiments were performed to determine the Mn requirement according to the phase (one at 20 days and 20-40 days of age). For each phase, 750 broilers were used. The treatments were defined by the supplementation of 0, 35, 70, 105 and 140 mg of Mn/kg as MnSO4. To determine the Mn requirement, feed intake, weight gain, feed conversion, viability and concentration of Mn in the tibia and liver, bone resistance, ash concentration in the tibia and alkaline phosphatase activity were analyzed. No effect of dietary Mn concentration on performance analyzes was observed in any of the production phases. The estimate of the Mn requirement for broilers from one to 20 days of age was 81.32 mg of Mn/kg for bone strength, 97.9 mg of Mn/kg for bone ash, 126.96 mg of Mn/kg for the concentration of Mn in the tibia and 149.45 mg of Mn/kg for concentration of Mn in the liver. In the period of 20 to 40 days the requirement estimate was 73.93 mg of Mn/kg for bone resistance and 151.4 mg of Mn/kg for Mn concentration in the tibia. The inclusion of Mn is only justified to improve bone strength, with a requirement of 81.32 mg of Mn/kg for the period of one to 20 days and 73.93 mg of Mn/kg for the period of 20 to 40 days. The RB of MnProt, compared to MnSO4, was determined in broilers from one to 20 days. 1350 broilers were used, and the diets were supplemented with 0, 35, 70, 105 and 140 mg of Mn/kg of feed as MnSO4 and as MnProt. The weight gain, feed intake, feed conversion, bone resistance and Mn concentration in the tibia and liver were evaluated. In addition, the concentration of type I collagen in the tibia was evaluated. No differences were observed for the performance variables nor for the concentration of type I collagen, regardless of the source and level of supplementation used. The RB of MnProt based on bone strength was 111%, based on the Mn concentration in the liver was 128% and based on the Mn concentration in the tibia was 105%. MnProt is more bioavailable than MnSO4